Basic research for designing the erbium doped fiber amplifier in long distance cable communications - Sterian, Andreea-Rodica (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The paper presents some of the author results obtained in the research on the optical fiber amplifiers and Quantum Well (QW) laser diodes used in long distance optical communications as those transoceanic and other applications. Based on the mathematical models of the Erbium Doped Fiber Amplifier (EDFA) and of the QW laser diodes, implemented in software (especially, MATHLAB and MATHCAD but also in SIMULINK and SPICE), we get the operational diagrams and parameters of the specified devices and structures. For example, the classic Runge-Kutta method has been successfully used for numerical simulation of complex nonlinear dynamics in fiber optic lasers.The obtained results are important in the design and characterization of the optical fiber communication systems, as those of the optical cables used in the naval and civil engineering.